Histone Chaperone NAP1 Mediates Sister Chromatid Resolution by Counteracting Protein Phosphatase 2A. - Moshkin, Y.M.; Doyen, C.M.; Kan, T.W.; Chalkley, G.E.; Sap, K.; Bezstarosti, K.; Demmers, J.A.; Ozgur, Z.; van Ijcken, W.F.; Verrijzer, C.P. (PLoS Genetics, 2013)
Chromosome duplication and transmission into daughter cells requires the precisely orchestrated binding and release of cohesin. We found that the Drosophila histone chaperone NAP1 is required for cohesin release and sister chromatid resolution during mitosis. Genome-wide surveys revealed that NAP1 and cohesin co-localize at multiple genomic loci. Proteomic and biochemical analysis established that NAP1 associates with the full cohesin complex, but it also forms a separate complex with the cohesin subunit stromalin (SA). NAP1 binding to cohesin is cell-cycle regulated and increases during G2/M phase. This causes the dissociation of protein phosphatase 2A (PP2A) from cohesin, increased phosphorylation of SA and cohesin removal in early mitosis. PP2A depletion led to a loss of centromeric cohesion. The distinct mitotic phenotypes caused by the loss of either PP2A or NAP1, were both rescued by their concomitant depletion. We conclude that the balanced antagonism between NAP1 and PP2A controls cohesin dissociation during mitosis.